2008
DOI: 10.1063/1.2829785
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structures of supersaturated ZnO–Al2O3 solid solutions

Abstract: Supersaturated ZnO-Al 2 O 3 ͑Ͼ20 at. % Al͒ thin films are grown by pulsed laser deposition technique on silica glass substrates at 600°C. They are characterized by combining x-ray diffraction, Al-K edge x-ray absorption near edge structures ͑XANESs͒, high resolution transmission electron microscope ͑TEM͒ imaging, TEM analysis, and a series of first principles calculations. The films are composed of textured wurtzite grains with c planes parallel to the substrate. The distance between c planes expands significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 28 publications
5
38
0
Order By: Relevance
“…Conversely, further increases in T g would significantly promote diffusion of the adatoms and precursors, leading to migration of ions in the bulk films, and desorption of Zn at the growth surface. Consequently, excess Al may degrade the film crystallinity by forming local atomic structures similar to a homologous phase ((ZnO) m Al 2 O 3 ) [14,15]. The effect of inserting homologous phases in a ZnO film would be to increase the out-of-plane dimension of the film.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, further increases in T g would significantly promote diffusion of the adatoms and precursors, leading to migration of ions in the bulk films, and desorption of Zn at the growth surface. Consequently, excess Al may degrade the film crystallinity by forming local atomic structures similar to a homologous phase ((ZnO) m Al 2 O 3 ) [14,15]. The effect of inserting homologous phases in a ZnO film would be to increase the out-of-plane dimension of the film.…”
Section: Resultsmentioning
confidence: 99%
“…At higher Al doping concentration above 3%, a decrease of the intensity of the (100) diffraction peak indicates a degeneration of the crystal quality; as a consequence, an increase of the resistivity was shown in Figure  4. The reason for the increase of the resistivity at high Al concentration is probably related to the formation of Zn vacancy acceptors or the formation of homologous phase like ZnAl x O y or Al 2 O 3 in the AZO films [9,22]. …”
Section: Resultsmentioning
confidence: 99%
“…As a wide-bandgap semiconductor material, ZnAl 2 O 4 was also used as host of phosphors doping with Mn and rare earth ions [5,6]. AZO and ZnAl 2 O 4 thin films have been deposited by different techniques [7], such as sol–gel coating [8], pulsed laser deposition [9], chemical vapor deposition [10], radio-frequency sputtering [11], and atomic layer deposition (ALD) [12,13]. Recently, ALD technology has been employed to grow transparent conductive AZO films with low resistivity in the order of 10 −3 Ω·cm [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The Zn-rich alloy was recently grown by pulsed laser deposition in the work of Yoshioka et al [104], where a superlattice structure was identified, which is consistent with the homologous crystal structure models developed for the In and Ga compounds, as later verified by electronic structure calculations [105]. There is growing evidence for the presence of the homologous phase in typical Aldoped ZnO samples [106,107], which can contribute to lower than expected electron carrier concentrations: excess electrons are compensated by additional oxygen incorporation in to the lattice.…”
Section: Rules Governing Structure Formation Crystalline Multi-componmentioning
confidence: 99%